2009
DOI: 10.1039/b918358b
|View full text |Cite
|
Sign up to set email alerts
|

Palladium(ii)-catalyzed coupling reactions with a chelating vinyl ether and arylboronic acids: a new Heck/Suzuki domino diarylation reaction

Abstract: A mild and novel palladium(II)-catalyzed domino Heck/Suzuki alpha,beta-diarylation-reduction of a dimethylaminoethyl substituted chelating vinyl ether was developed by using electron-rich arylboronic acids in combination with p-benzoquinone. Based on the preparative results, a catalytic cycle is proposed. Further, highly regioselective palladium(II)-catalyzed alpha- or beta-monoarylation of the chelating vinyl ether was achieved using either a bidentate ligand or by employing ligand-less conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 29 publications
4
30
0
Order By: Relevance
“…This suggests that performing the reaction in DMF strongly hampers the production of 4 in favour of 3 , regardless of the addition of BQ to the reaction mixture. This is in line with the experimental results that showed that polar solvents increased the production of 3 6, 7. However, an energy difference of 13 kJ mol −1 should result in the almost complete selectivity of 3 , which indicates an overestimation of the calculated difference in free energy.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…This suggests that performing the reaction in DMF strongly hampers the production of 4 in favour of 3 , regardless of the addition of BQ to the reaction mixture. This is in line with the experimental results that showed that polar solvents increased the production of 3 6, 7. However, an energy difference of 13 kJ mol −1 should result in the almost complete selectivity of 3 , which indicates an overestimation of the calculated difference in free energy.…”
Section: Resultssupporting
confidence: 90%
“…The transition state (TS) for internal phenylation ( TS-a ) was found to be 25 kJ mol −1 higher in energy than the TS for terminal phenylation ( TS-b ). The free-energy profile is presented in Figure 1 and is in agreement with the experimental outcome of the reaction when the oxidative Heck product is formed, given that when chelation from the alkene is feasible, that is, no strongly coordinating bidentate ligand is present in the reaction mixture, the terminal product is formed with a 3 / 2 selectivity of >50:1 6. This is equivalent to the selectivity obtained with the Pd 0 -catalysed Mizoroki–Heck reaction 5a, 11.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…Previously, our research group reported a novel palladium(II)-catalyzed domino Heck/Suzuki β,α-diarylation of an achiral dimethylaminoethyl-substituted vinyl ether using an excess of arylboronic acid in combination with p -BQ 10c. For the domino Heck/Suzuki reaction, we proposed a mechanism involving a chelation-controlled carbopalladation step,11 which was supported by recent density functional theory (DFT) calculations, highlighting the crucial role of p -BQ in the catalytic process 12.…”
Section: Introductionmentioning
confidence: 99%